The G-Box Transcriptional Regulatory Code in Arabidopsis. Issue 2 (1st September 2017) - Ezer, Daphne; Shepherd, Samuel J.K.; Brestovitsky, Anna; Dickinson, Patrick; Cortijo, Sandra; Charoensawan, Varodom; Box, Mathew S.; Biswas, Surojit; Jaeger, Katja E.; Wigge, Philip A.
Abstract : DNA-binding and gene expression data predict which bHLH or bZIP transcription factors are likely regulators of genes near perfect G-box (CACGTG) motifs. Abstract: Plants have significantly more transcription factor (TF ) families than animals and fungi, and plant TF families tend to contain more genes; these expansions are linked to adaptation to environmental stressors. Many TF family members bind to similar or identical sequence motifs, such as G-boxes (CACGTG), so it is difficult to predict regulatory relationships. We determined that the flanking sequences near G-boxes help determine in vitro specificity but that this is insufficient to predict the transcription pattern of genes near G-boxes. Therefore, we constructed a gene regulatory network that identifies the set of bZIPs and bHLHs that are most predictive of the expression of genes downstream of perfect G-boxes. This network accurately predicts transcriptional patterns and reconstructs known regulatory subnetworks. Finally, we present Ara-BOX-cis (araboxcis.org), a Web site that provides interactive visualizations of the G-box regulatory network, a useful resource for generating predictions for gene regulatory relations.